Micro-orchards for community connection and environmental justice - Ashley Williamson (Urban Food Systems Symposium, 2022)
As our climate heats up, and extreme weather patterns become more routine, cities across America are becoming challenged by their aging infrastructure that was never designed to handle such extreme heat waves and severe flooding. Unfortunately, these extreme weather conditions have a disproportionate impact on people of color and people who live in disinvested communities. The Giving Grove launched in 2013 with a vision to establish environmentally beneficial, sustainable orchards in urban neighborhoods that are vulnerable to environmental changes and health inequities. The idea was simple: work side-by-side with resident leaders and provide them with the disease-resistant trees, tools, and holistic methods they need to care for their own little orchards. The impact exceeded expectations, establishing a nationwide network of food-producing urban greenspaces that increase tree canopy, sequester carbon dioxide, improve and stabilize soil, and reduce stormwater runoff. Today there are more than 400 of these little orchards taking root in six cities, with four more cities joining the network this spring. Combined, the 429 current sites have the capacity to produce over 3.75 million servings of fresh food annually, available for free and within walking distance of residents. Neighborhood interest and involvement drives the creation and maintenance of all Giving Grove orchards. Community leaders champion and maintain the sites, encouraging lasting, generational change. Through this approach, neighbors have more opportunities to meet one another and build relationships, creating a stronger network of community connections. Often located in neighborhoods that suffer the consequences of urban heat zones and low tree canopy, orchards are beneficial to the environment in the surrounding area. With an average of 15 trees, each orchard can sequester approximately 29 tons of carbon over 25 years and absorb 500 gallons of water per storm, reducing urban flooding. Trees also help reduce urban air temperatures by 10 degrees on a hot summer day. With dozens (or hundreds) of neighborhood orchards across a city, the impact grows exponentially. Our team is passionate about the ways an orchard can benefit communities that invite us to work with them. Affiliates in nine cities, from coast to coast, are helping create a powerful network that develops best practices and deep knowledge going directly on (and into) the ground of participating communities, rooting resiliency and sustainability.
Keywords: climate change; food insecurity; urban; neighborhood orchards; community orchards